Feminist Movements and Gender Perspective: Integrating the Debate Across the Translators’ Training Curriculum [Movimientos Feministas y Enfoques de Género: Integración del Debate en Las Líneas Curriculares Para la Formación de Traductores en Chile] - Contreras-Torregrosa, M; Basaure-Cabero, R (Universidad de Antioquia, 2019)
Translators’ training cannot be isolated from the constantly changing international context or from social demands, as these professionals will be mediating agents between different linguistic, cultural and ideological realities. In this regard, the issue of gender awareness and feminist movements should be part of the curriculum and research lines in this field worldwide. However, this has not been actively reflected on Latin American universities. This study seeks to analyze this issue, particularly from the Chilean perspective, and to establish guidelines to integrate it in the curriculum by proposing a specific course, with relevant undergraduate teaching methodologies that will also lead to research development in that field. Regarding the methodology, the study is based on the analysis of the current debate on gender awareness issues in Chilean Translation programs, from a curricular point of view. From these results, the process of developing and implementing an elective course that considers this topic as the central part of the training is addressed in the program of BA in Translation Studies of Universidad de Santiago de Chile. © 2019 Universidad de Antioquia. All rights reserved.